Sistem Manajemen Pembiayaan Sekolah Gratis - Ahmad Syaddad (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2020)
SMA Selamat Pagi Indonesia Kota Batu is one of the few free schools that dare to make decisions by waiving all tuition fees and living expenses for students from orphaned and disadvantaged backgrounds. This research aims to explain and review the free school financing management system (case study at Sma Selamat Pagi Indonesia Kota Batu) with the scope of planning and implementation of free school financing. This study uses a qualitative and quantitative descriptive approach with a single type of instrumental case study. Data collection conducted using interviews, and documentation. Data analysis techniques include data reduction, data presentation, and data verification. The results showed that: 1) financing planning is prepared and poured into the budget held at the end of the year by setting the program along with the details of the program budget. This plan involves the school's development team, namely the principal, the treasurer, the entire Waka, the teacher representative of choice and known by the foundation. The source of financing is obtained from: Foundation (donor rank silver director and above MLM company by 5% deducted from their income, and the foundation's independent business namely PT. Thanks to Continued Abundance), the Government (BOSDA and BOSNAS), the Papuan Artifact Program, and the community. 2) In its implementation the treasurer uses general ledger and ledger for receipt and expenditure of the budget using a digital system. The budget disbursement procedure is carried out at three stages, namely making proposals, approval of the principal, and disbursement of the budget through the treasurer and then reported in the form of LPJ. The cost of education for the needs of students in a year is Rp. 7,950,930,000. The behavior of education financing shows direct cost expenditure on improving the quality of education and learning resources of students by Rp.593,661,450 with a percentage figure of 72.4%.